ACOMPANHAMENTO DE ADOLESCENTES EM USO DE IMPLANON EM DOURADOS – MATO GROSSO DO SUL - Rolim Baracho, Eduarda; Henrique Campos das Neves, Paulo; Avila Silva, Polia; Maria Ribera Lopes Spessoto, Márcia; Faria Gonçalves, Mariana; Luiza Araújo Gomes, Pâmela (ANAIS DO ENIC, 2026)
-